In vivo localization and identification of SUMOylated proteins in the brain of His6-HA-SUMO1 knock-in mice - Tirard, Marilyn; Hsiao, He-Hsuan; Nikolov, Miroslav; Urlaub, Henning; Melchior, Frauke; Brose, Nils (Proceedings of the National Academy of Sciences of the United States of America, 2012)
SUMOylation, an essential posttranslational protein modification, is involved in many eukaryotic cellular signaling pathways. The identification of SUMOylated proteins is difficult, because SUMOylation sites in proteins are hard to predict, SUMOylated protein states are transient in vivo and labile in vitro, only a small substrate fraction is SUMOylated in vivo, and identification tools for natively SUMOylated proteins are rare. To solve these problems, we generated knock-in mice expressing His6-HA-SUMO1. By anti-HA immunostaining, we show that SUMO1 conjugates in neurons are only detectable in nuclei and annulate lamellae. By anti-HA affinity purification, we identified several hundred candidate SUMO1 substrates, of which we validated Smchd1, Ctip2, TIF1γ, and Zbtb20 as novel substrates. The knock-in mouse represents an excellent mammalian model for studies on SUMO1 localization and screens for SUMO1 conjugates in vivo.